(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
There is abundant information about encouraging children to read books. In this article, we explore how the formation and improvement of a child’s interest in reading has been thoroughly studied not only in modern psychology but also in the heritage of Eastern thinkers. Our attention was particularly drawn to the ideas put forward by our scholars Abu Nasr Farabi and Abu Rayhan Beruni, which serve as an important theoretical foundation for stimulating interest in reading through psychological mechanisms today. Al-Farabi distinguished between two stages of cognition - sensory and mental, emphasizing the high role and importance of the human intellect in the process of cognition. He substantiated that personal perfection is achieved through the pursuit of knowledge, being erudite, and correctly directing one’s mind. The thinker urged people to be educated and presented instructive ideas about the role of students in society and their inherent qualities.